Chromatographically separable rotamers of an unhindered amide - Geffe, Mario; Andernach, Lars; Trapp, Oliver; Opatz, Till (Beilstein journal of organic chemistry, 2014)
Surprisingly stable formamide rotamers were encountered in the tetrahydroisoquinoline and morphinan series of alkaloids. We investigated the hindered rotation around the amide bond by dynamic high-performance liquid chromatography (DHPLC) and kinetic measurements of the interconversion of the rotamers which can readily be separated by HPLC as well as TLC. The experimental results of the different methods were compared to each other as well as to results obtained by DFT calculations.